2020
DOI: 10.1016/j.transci.2019.102716
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived bio-products: Classification update, applications, concerns and new perspectives

Abstract: Platelet derived bio-products in the form of platelet rich plasma, plasma rich in growth factors, or plasma-free platelet releasates, are being studied worldwide with the aim of proving their efficacy in tissue regeneration within many different clinical areas, such as traumatology, maxillofacial surgery, ophthalmology, dermatology and otorhinolaryngology, amongst others. The current lack of consensus in the preparation method and application form, or in the quality assessment of each bio-product, precludes ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 131 publications
0
34
0
1
Order By: Relevance
“…An intense debate for a consensus definition and classification of the plethora of PRP-related products of clinical use persists in the scientific community in the past decade (8,(56)(57)(58)(59)(60)(61)(62). From Mishra et al (63) to Kon et al (64), different classifications methods have been proposed for human PRP.…”
Section: Classification Of Platelet Concentrates In Human Regenerativmentioning
confidence: 99%
“…An intense debate for a consensus definition and classification of the plethora of PRP-related products of clinical use persists in the scientific community in the past decade (8,(56)(57)(58)(59)(60)(61)(62). From Mishra et al (63) to Kon et al (64), different classifications methods have been proposed for human PRP.…”
Section: Classification Of Platelet Concentrates In Human Regenerativmentioning
confidence: 99%
“…PLTs and artificial PLTs can be converted into drug carriers, given their ability to target and migrate to sites of injuries or disease [121][122][123]. In addition, their newly-identified functions in immune modulation, inflammation, cancer, and tissue regeneration [124][125][126] open the door to the in vitro production of fine-tuned PLTs, both at the receptor and the cargo levels, that can potentially modulate these pathological states [127][128][129].…”
Section: Artificial Platelets and Applications Beyond Transfusion Med...mentioning
confidence: 99%
“…PRP has various growth factors, including fibroblast growth factor, epidermal growth factor, vascular endothelial growth factor, platelet-derived growth factor, transforming growth factor-β, and insulin-like growth factor [ 27 ]. Despite the focused use of PRP, the efficacy of PRP remains under debate because of the lack of consensus in the optimal preparation condition for tissue regeneration [ 28 ]. The clear effect of PRP on osteogenic differentiation remains to be elucidated and some studies have reported conflicting results about the effect of PRP on osteogenesis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%